Community sport and physical activity programs as sites of integration: A meta-synthesis of qualitative research conducted with forced migrants. (November 2020) - Middleton, Thierry.R.F.; Petersen, Brennan; Schinke, Robert J.; Kao, San Fu; Giffin, Cole
Abstract: Objectives: Sport involvement has been touted as a way of helping forced migrants (i.e., refugees and asylum seekers) integrate into their host communities. Our aim was to synthesize multi-disciplinary qualitative research and through a sport and exercise psychology lens develop novel interdisciplinary insights of how sport and physical activity may become an integrative context for forced migrants. Design: Working from a social constructionist epistemological position, a meta-synthesis of multi-disciplinary qualitative research was conducted. Methods: A literature search of seven electronic databases resulted in 23 peer-reviewed journal articles published since 1990 that met the inclusion criteria and were included in the synthesis. Results: Our descriptive synthesis based on the preceding analysis of multi-disciplinary literature is presented through three themes: (a) the beneficial role of sport in the life stories of forced migrants, (b) barriers to sport and physical activity, and (c) sport as an integrative context. Discussion and conclusion: Our interpretive meta-synthesis provides insight into the need for a critical approach to understanding how host communities may go about developing safe sport and physical activity contexts that support the integration of forced migrants. Highlights: Meta-synthesis of qualitative research exploring forced migrant sport and physical activity participation. Synthesizes findings related to benefits of, and barriers to, sport and physical activity participation. Describes and interprets previous findings of how sport may or may not foster integration. Discusses the importance of examining forced migrants' life stories through a critical lens. Provides insight into importance of fostering feelings of safety for forced migrants.